Novel Emergency Medicine Curriculum Utilizing Self-Directed Learning and the Flipped Classroom Method: Genitourinary Emergencies Small Group Module - Andrew King; Geremiha Emerson; Jennifer Mitzman; Eric Adkins; Alyssa Tyransky; Robert Cooper; Nicholas Kman; Christopher Paul; Ashish Panchal; Michael Barrie; Sorabh Khandelwal; Diane Gorgas; et al. (eScholarship Publishing, University of California, 2017)
Audience: This curriculum, created and implemented at The Ohio State University Wexner Medical Center, was designed to educate our emergency medicine (EM) residents, PGY-1 to PGY-3, as well as medical students. Introduction: In 2013, there were over 6 million Emergency Department visits in the United States which resulted in a primary diagnosis of the genitourinary system. This represents 5.2% of all Emergency Department visits.1 Residents must be proficient in the differential diagnosis and management of the wide variety of genitourinary emergencies. This flipped classroom curricular model emphasizes self-directed learning activities completed by learners, followed by small group discussions pertaining to the topic reviewed. The active learning fostered by this curriculum increases faculty and learner engagement and interaction time typically absent in traditional lecture-based formats.2-4 Studies have revealed that the application of knowledge through case studies, personal interaction with content experts, and integrated questions are effective learning strategies for emergency medicine residents.4-6 The Ohio State University Wexner Medical Center EM Residency didactic curriculum recently transitioned to a "flipped classroom" approach.7-10 We created this innovative curriculum aimed to improve our residency education program and to share educational resources with other EM residency programs. Our curriculum utilizes an 18-month curricular cycle to cover the defined emergency medicine content. The flipped classroom curriculum maximizes didactic time and resident engagement, fosters intellectual curiosity and active learning, and meets the needs of today's learners. 3,6,11 Objectives: We aim to teach the presentation and management of genitourinary emergencies through the creation of a flipped classroom design. This unique, innovative curriculum utilizes resources chosen by education faculty and resident learners, study questions, real-life experiences, and small group discussions in place of traditional lectures. In doing so, a goal of the curriculum is to encourage self-directed learning, improve understanding and knowledge retention, and improve the educational experience of our residents. Methods: The educational strategies used in this curriculum include: small group modules authored by education faculty and content experts based on the core emergency medicine content. This program also includes resident submitted questions that were developed during review of the content. The Socratic Method, used during small group sessions, encourages active participation; small groups also focus on the synthesis and application of knowledge through the discussion of real life experiences. The use of free open access medical education (FOAM) resources allows learners to work at their own pace and maximize autonomy.